Pengaruh Bahan Kemasan Berbeda terhadap Mutu Bandeng Presto dengan Pengemasan Vakum pada Suhu Dingin - Nursafira, Julia; Munandar, Aris; Surilayani, Dini (Sam Ratulangi University, 2021)
Bandeng Presto is a form of processed fishery products made from milkfish with the addition of salt, spices and through heating and pressure processing. Period the storage for bandeng presto is around 2-5 days. Low sheilf can be caused by high nutrient content, as well as enviromental influences and contamination of microorganism. Purpose of this study was to determine the type of packaging material that is best for the quality of bandeng presto with optimal shelf life. This study usedÂ factorial completely randomized design with 2 factors, namely packaging (polypropylene and polyethylene) with storage time (0.7.14 and 21 Days). The parameters observed in this study were organoleptic, moisture content, ash content, fat content, protein content, and total plate count (TPC).The results of this study indicate that the treatment using the type of polypropylene packaging with the vacuum technique is a treatment with an optimal shelf life of 21 days at cold temperatures and has characteristics value his a moisture content value 61.09%, ash content 4.78%, fat content 6.56%, protein content 34.60%, microbes total 4.21x105colony/gand bandeng presto have the appearance of golden yellow, less fresh odor, bland taste, dense texture, slightly mushy and dried mucus.